Transfusion in critical care: Past, present and future. Issue 6 (18th November 2020) - Shah, Akshay; Oczkowski, Simon; Aubron, Cecile; Vlaar, Alexander P.; Dionne, Joanna C.; ,
Abstract: Anaemia and coagulopathy are common in critically ill patients and are associated with poor outcomes, including increased risk of mortality, myocardial infarction, failure to be liberated from mechanical ventilation and poor physical recovery. Transfusion of blood and blood products remains the corner stone of anaemia and coagulopathy treatment in critical care. However, determining when the benefits of transfusion outweigh the risks of anaemia may be challenging in some critically ill patients. Therefore, the European Society of Intensive Care Medicine prioritised the development of a clinical practice guideline to address anaemia and coagulopathy in non‐bleeding critically ill patients. The aims of this article are to: (1) review the evolution of transfusion practice in critical care and the direction for future developments in this important area of transfusion medicine and (2) to provide a brief synopsis of the guideline development process and recommendations in a format designed for busy clinicians and blood bank staff. These clinical practice guidelines provide recommendations to clinicians on how best to manage non‐bleeding critically ill patients at the bedside. More research is needed on alternative transfusion targets, use of transfusions in special populations (e.g., acute neurological injury, acute coronary syndromes), use of anaemia prevention strategies and point‐of‐care interventions to guide transfusion strategies.